Impact of human activities on coral metric diversity and disease prevalence in Padamarang and Wangi Wangi Islands, Southeast Sulawesi, Indonesia - RATNA DIYAH PALUPI; LA ODE MUHAMMAD YASIR HAYA; ANINDITIA SABDANINGSIH; DIAH AYUNINGRUM; AGUS SABDONO (Society for Indonesian Biodiversity, 2025)
Abstract. Palupi RD, Haya LOMY, Sabdaningsih A, Ayuningrum D, Sabdono A. 2025. Impact of human activities on coral metric diversity and disease prevalence in Padamarang and Wangi Wangi Islands, Southeast Sulawesi, Indonesia. Biodiversitas 26: 1334-1342. Coral diseases are emerging throughout Southeast Sulawesi, Indonesia which might be due to local anthropogenic stressors. This study aims to investigate the impact of anthropogenic stress on coral cover and the prevalence of coral disease in Padamarang (uninhabited) and Wangi Wangi (inhabited) Islands. Data were observed and collected by Scuba Diving in these sites in February-March 2023. The prevalence of diseases was calculated as the mean percentage of coral colonies affected by disease per 100 m2 belt transect. The findings indicated both sites showed relatively similar values for Genus Richness, H-index, and Evenness, suggesting comparable ecological diversity across the sites. Specifically, Padamarang exhibited a slightly lower Genus Richness (11.24 vs 12.48), and its Evenness value was also marginally higher (0.61 vs 0.58 in Wangi Wangi). However, the statistical significance of the abundance differences suggests that Wangi Wangi may support a denser coral population overall. Porites sp. showed a particularly high rate of infection, with White Syndrome, White Band Disease, and Black Band Disease being the most frequently observed illnesses. It is expected that the results of this research will provide better insight into the impact of anthropogenic stress on coral reef health and encourage further conservation efforts to safeguard this important coral ecosystem.